Public education messages aimed at smartphone use among young drivers: A mixed methods exploration of their effectiveness. (January 2019) - Gauld, Cassandra S.; Lewis, Ioni M.; White, Katherine M.; Fleiter, Judy J.; Watson, Barry
Highlights: Highlights the importance of testing new message concepts with the target audience. Applies Step 3 of the Step Approach to Message Design and Testing. Mixed methods approach examines thoughts and feelings about the messages. Messages with positive behaviour and positive emotions especially persuasive. Abstract: The main aim of this study was to concept test nine public education messages; with three different messages targeting each of three salient underlying beliefs in accordance with the Step Approach to Message Design and Testing (SatMDT) framework. The underlying beliefs were: (1) believing you are a good driver would encourage a young driver to monitor/read and respond to social interactive technology while driving; (2) slow-moving traffic would encourage a young driver to monitor/read and respond to social interactive technology while driving; and, (3) friends and peers would approve of a young driver monitoring/reading and responding to communications on their smartphone. Consistent with the SatMDT, the testing aimed to establish which three messages (each targeting a different underlying belief) young drivers reported as being the most effective. A mixed methods approach was utilised to provide an in-depth examination of individuals' thoughts and feelings about the messages, with such responses assessed via an individual self-report survey and focus group discussions/interviews. Participants ( N  = 33; 19F, 14 M) were aged 17–25 years, had a current driver's licence, owned a smartphone, and resided in the Australian state of Queensland. Means for each of the survey items were compared across message concepts to determine which ones were rated highest. Focus group discussion/interview responses underwent a data-led thematic analysis. The results of the quantitative and qualitative analyses were integrated to identify three messages that were deemed the most effective, one for each of the three underlying beliefs. Each of these three messages elicited positive emotion and modelled positive behaviour. This research highlights the importance of concept testing message content with the target audience. The results support current research that suggests road safety messages modelling positive behaviour and eliciting positive emotions may be especially persuasive for young drivers.